P2Y6R Involvement in Glymphatic Pathway Clearance of Amyloid: Molecular and Behavioral Implications for Alzheimer’s Disease. - DesRuisseaux, Libby A. (Tufts Archival Research Center, 2018)
Alzheimer’s Disease (AD), which is characterized by a progressive impairment in episodic memory as well as other behavioral and cognitive functions, is the most common cause of dementia, affecting about 5.5million people in 2017. It is thought that AD is the result of the accumulation of neurotoxic amyloid protein in the brain resulting from impaired clearance and homeostatic mechanisms in the brain. Dong et al. (in preparation) have identified a prodrug, GC021109, that has been shown to reverse the pathological accumulation of amyloid in the brain and the corresponding decrease of amyloid in the cerebrospinal fluid that is characteristic of AD in both preclinical mouse trials and human phase 1 clinical trials. GC021109 is an activator of the P2Y6 receptor. The relationship between P2Y6 receptors and amyloid clearance is not yet known. The goal of the current project was to elucidate the connection between P2Y6R activity and the glymphatic pathway, a waste clearance pathway in the brain, to determine whether P2Y6R is modulating amyloid clearance via this pathway. Fluorescent tracers were injected into the brain or CSF of mice and the tracers' circulation throughout the glymphatic pathway was compared with and without GC021109 treatment to determine if treatment yielded increased glymphatic pathway circulation of the tracers. Behavioral assessments were also conducted on mouse models of AD to determine the effect GC021109 has on behavioral and cognitive symptoms of AD.